Are glove perforations equivalent to sharp injuries: results from a study in maxillofacial surgery - Chhabra, Shruti; Chhabra, Naveen; Thapar, Deepti (International Journal of Infection Control, 2011)
The objective of the present study was to remove the ambiguity in usage of terms Glove perforations (GP) and Sharp injuries (SI) equivalently. A 6 months prospective study was conducted involving the use of double gloving practice for the procedures needing medical sharps in maxillofacial surgery. Total of 270 procedures were performed. GP’s and SI’s were analysed. The data revealed total of 400 GP’s including 290 outer GP and 110 inner GP and 80 SI. Out of 80 SI, 65 were superficial and 15 were deep injuries. Out of total 270 patients, 25 were high risk patients. Only 5 significant exposures were observed which were a part of high risk patient group. This study concludes: Every GP is not always SI but every SI is a GP. Risk of SI increases with inner GP but it is also not necessary that every inner GP leads to SI. A modified surveillance and a new algorithm are also proposed which can be a part of guidelines for occupational safety and health.